3x + 4y + 5 = 0; y = x + 4

(ii) 3x + 4y + 5 = 0; y = x + 4

3x + 4y = -  5
X
 - 3
5
1
Y
1
-5
-2
(X,Y)
(-3,1)
(5,-5)
(1,-2)

Put x = - 3
3(-3) + 4y = - 5
-9 + 4y = - 5
4y = -5 + 9
4y = 4
y = 4/4
y = 1
Put x = 5
3(5) + 4y = - 5
15 + 4y = - 5
4y = - 5 – 15
4y = - 20
y = -20/4
y = - 5  

Put x = 1
3(1) + 4y = - 5
3 + 4y = - 5
4y = - 5 – 3
4y = - 8
y = -8/4
y = - 2  

y = x + 4  
X
0
1
2
Y
4
5
6
(X,Y)
(0,4)
(1,5)
(2,6)


Put x = 0
y =  0 + 4
y = 4
Put x = 1
y = 1 + 4
y = 5
Put x = 2
y = 2 + 4
y = 6






 x = - 3  and y = 1 is the solution of given simultaneous equations.